Association between surgical approach and survival following resection of abdominopelvic malignancies. Issue 4 (22nd January 2020) - Yuce, Tarik K.; Ellis, Ryan J.; Chung, Jeanette; Merkow, Ryan P.; Yang, Anthony D.; Soper, Nathaniel J.; Tanner, Edward J.; Schaeffer, Edward M.; Bilimoria, Karl Y.; Auffenberg, Gregory B.
Abstract: Background and Objectives: Recent studies demonstrating decreased survival following minimally invasive surgery (MIS) for cervical cancer have generated concern regarding oncologic efficacy of MIS. Our objective was to evaluate the association between surgical approach and 5‐year survival following resection of abdominopelvic malignancies. Methods: Patients with stage I or II adenocarcinoma of the prostate, colon, rectum, and stage IA2 or IB1 cervical cancer from 2010‐2015 were identified from the National Cancer Data Base. The association between surgical approach and 5‐year survival was assessed using propensity‐score‐matched cohorts. Distributions were compared using logistic regression. Hazard ratio for death was estimated using Cox proportional‐hazard models. Results: The rate of deaths at 5 years was 3.4% following radical prostatectomy, 22.9% following colectomy, 18.6% following proctectomy, and 6.8% following radical hysterectomy. Open surgery was associated with worse survival following radical prostatectomy (HR, 1.18; 95% CI, 1.05‐1.33; P  = .005), colectomy (HR, 1.45; 95% CI, 1.39‐1.51; P  < .001), and proctectomy (HR, 1.28; 95% CI, 1.10‐1.50; P  = .002); however, open surgery was associated with improved survival following radical hysterectomy (HR, 0.61; 95% CI, 0.44‐0.82; P  = .003). Conclusions: These results suggest that MIS is an acceptable approach in selected patients with prostate, colon, and rectal cancers, while concerns regarding MIS resection of cervical cancer appear warranted.